Investigation on the sustainable use of different sizes of sawdust aggregates in eco-friendly foam concretes: Physico-mechanical, thermal insulation and durability characteristics - Ozkan, Iffet Gamze Mutevelli; Aldemir, Kiymet; Alhasan, Omar; Benli, Ahmet; Bayraktar, Oguzhan Yavuz; Yilmazoglu, Mehmet Ugur; Kaplan, Gokhan (Elsevier BV, 2024)
The extensive mining of natural resources, such as sand, for the construction industry, poses a hazard to the environment. To preserve the environment, the researcher must thus take into account the use of industrial byproducts rather than natural materials. The use of sawdust (SD) produced by the wood industry in foam concretes (FC) has been investigated in this study. This study examined the physical, mechanical, thermal, microstructural and durability characteristics of FC containing SD as a replacement of silica sand (SS) in the rates of 0, 25, 50 and 100 %. Two different SD sizes of 0–4 mm (SD4) and 0–1 mm (SD1) were used in the fabrication of FC mixtures. Protein-based foam agent was used to create FC mixtures. Fourteen mixtures with a 0.6 water/binder (w/b) ratio were produced at two different cement contents of 400 kg/m3 and 500 kg/m3. The fresh, mechanical, physical, and sorptivity characteristics of the FC mixtures were investigated in relation to the impacts of cement dosage, SD size, and SD replacement levels of SS. Durability of FC against high temperature, sulfate attack and freeze-thaw cycles was assessed. Costs and CO2 emissions from the blends were also assessed. The outcomes revealed that a 25 %SD1 integrated FC mixture with a cement content of 500 kg/m3 generated the highest 28-day compressive strength of 3.56 MPa with a 20 % strength loss as per the Ref.500 mixture. 17 % lower thermal conductivity was gained with the inclusion of 100 %SD4 as per the Ref.400 mixture. The mixture with 50 %SD4 and 400 kg/m3 cement dosage exhibited the best resistance to high temperature. The mixture with 25 %SD1 and 400 kg/m3 cement dosage showed the best frost resistance. SD incorporated mixtures showed better durability performance than the reference mixtures.